Business Planning and Assessment of Its Impact on the Enterprise Financial Stability (Economics and region, 2020)
At the present stage of the company development as an open social and economic system the question of how existing methods of financial analysis meet the needs of users considering the dynamism and complexity of business processes remains relevant. The purpose of the article is study relationships between static and dynamic indicators of financial condition, to reflect its characteristics such as business activity and financial stability. The article defines the functional relationship between dynamic business activity indicators and static indicators of financial stability, grounds technique of factor analysis of financial stability. The economic content ratio of the assets turnover and equity is defined. The nature of its relationships with the dynamics of assets is considered. Both theoretically and practically it is determined that if the correlation of ratio of asset turnover and equity is bigger than the ratio of financial independence at the beginning of the period under study, the positive dynamics of the property will affect the company’s final financial stability and vice versa, if the ratio is less than the rate of financial independence at the beginning of the period under study, the impact of positive dynamics of property on the final financial stability will be positive. It is proposed to consider this dependence both for factor retrospective analysis and for financial stability forecasting.
Keywords: financial condition; financial stability; business activity; financial ratios; planning; impact assessment